A novel on-demand therapy for lifelong premature ejaculation using a miniature transperineal electrical stimulator-the vPatch: An as-treated analysis - Shechter, Arik; Mondaini, Nicola; Şerefoğlu, Ege Can; Gollan, Tal; Deutsch, Frederic; Appel, Boaz; Gruenwald, Ilan (Oxford University Press, 2023)
Background: While premature ejaculation (PE) is a common and disturbing sexual dysfunction in men, current available treatment modalities have limited efficacy and low treatment adherence. Aim: To assess the feasibility, safety, and efficacy of the vPatch, a miniaturized on-demand perineal transcutaneous electrical stimulation device for treating PE. Methods: This prospective bicenter international first-in-human clinical study consisted of 2 arms, was sham controlled, and had a randomized double-blind design. In terms of statistical power calculation, 59 patients aged 21 to 56 years (mean ± SD, 39.8 ± 9.28) with lifelong PE were included. During the initial visit, intravaginal ejaculatory latency time (IELT) was measured over a 2-week run-in period. Eligibility was confirmed in visit 2, based on IELT values, medical and sexual history, and patients’ individualized sensory and motor activation thresholds during perineal stimulation with the vPatch. Patients were randomized to the active (vPatch) and sham device groups in a 2:1 ratio, respectively. The vPatch device’s safety profile was determined by comparing the incidence of treatment-emergent adverse events. During visit 3, IELTs, Clinical Global Impression of Change scores, and Premature Ejaculation Profile questionnaire outcomes were recorded. Primary end points assessed vPatch device efficacy as mean change in geometric mean IELT; each person was compared with himself, with and without the device, and the sham group was compared with the active group. Outcomes: Outcomes included changes in IELT and Premature Ejaculation Profile before and after treatment, last visit Clinical Global Impression of Change scores, and vPatch safety profile. Results: Of 59 patients, 51 completed the study: 34 in the active group and 17 in the sham group. The baseline geometric mean IELT significantly increased from 67 to 123 seconds (P < .01) in the active group, as compared with an insignificant increase from 63 to 81 seconds (P = .17) in the sham group. The increase in mean IELT in the active group was significantly higher than in the sham group (56 vs 18 seconds, P = .01). IELT significantly increased by 3.1 times in the active vs sham group. The mean ratio of fold change (active:sham) was 1.4, significantly different from 1.0 (P = .02). No serious adverse events were reported. Clinical Implications: Therapeutic use of the vPatch during coitus may become an on-demand, noninvasive, and drug-free treatment for PE. Strengths and Limitations: To our knowledge, this is the first rigorous study investigating whether transcutaneous electrical stimulation during coitus could improve the symptoms of men with lifelong PE. The study is limited by the small number of patients, the exclusion of patients with acquired PE, the short-term follow up, and the use of a device based on a theoretic mechanism of action. Conclusion: We demonstrated the possibility to treat lifelong PE by prolonging coitus on demand, using electric stimulation of ejaculation muscles with the vPatch. Clinical trial registration: NCT03942367 (ClinicalTrials.gov).
Keywords: Drug Free; Electrical Muscle Stimulation; Medical Device; Noninvasive; Premature Ejaculation; Sexual Dysfunction; Therapy; Transcutaneous Electrical Stimulation